FOLLOWING FASHION FOR YOUTH AND TEENAGERS AS AN IMPORTANT EDUCATION FACTOR - Aliyeva, N.M (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2019)
The article deals with the education of the younger generation in terms of fashion. Based on the analysis of the available scientific literature, views on fashion among youth and adolescents are generalized, social factors affecting the consciousness of this age group of people are specified. Compared with middle-aged people, young people, as a rule, dress in bright and varied colors and use the best of the fashion trends of the East and West in clothes. This directly affects public opinion and the psychology of people. Modern young people are influenced by commercials that promote trending things and objects. In particular, adolescents imitate others. Extensive educational work is necessary to form the correct ideas about the style of dressing. It must be carried out together with parents. What matters is the nature of the teenager's leisure time, his interests, the social environment in which he revolves. It is necessary not to imitate fashion, but to study it from the point of view of one's worldview, tastes and views. For this, it is useful to conduct conversations, various events, where there is the opportunity to meet and discuss the necessary issues.